Asuhan Keperawatan pada Anak dengan Dengue Hemorragic Fever : Sebuah Studi Kasus - evi novia rahmawati (AKPER Pasar Rebo, 2020)
Background: Dengue Hemorrhagic Fever is an infection disease caused by dengue virus, infected by aedes aigypty and aedes albopictus widespread in the tropics and sub tropics Methods: The mrthod used is the qualitative method, during the month of February 2020 and place of research at RSUD pasar minggu Result: Diagnosis that occurs in cases of fluid volume deficiency is related to related loss through abnormal routes: increased capillary permeability, nutritional imbalances that are less than the body's needs are associated with difficult intake, and Knowledge deficiency is related to lack of knowledge resources:Dengue Hemorrhagic Fever Conclusion: Nursing care will succeed when the outcome criteria created can be achieved and to achieve success the outcome criteria require collaboration between other health teams